2021
DOI: 10.1007/s00296-021-04857-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of COVID-19 in patients with rheumatic diseases

Abstract: This study aimed to assess the baseline characteristics and clinical outcomes of coronavirus disease 2019 (COVID-19) in patients with rheumatic diseases and identify the risk factors associated with severe COVID-19 pneumonia. This was a retrospective study in a tertiary care center conducted through the period between March 2020 and November 2020 and included all adult patients with rheumatic diseases who tested positive on the COVID-19 polymerase chain reaction (PCR) test. We assessed the patients’ demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
3
19
0
4
Order By: Relevance
“…In most studies, including ours, comorbidities and older age have been found to be independent risk factors for COVID-19-related poor outcomes in patients with IMIDs. 13 , 14 Moreover, we identified no association between baseline treatment, including immunosuppressive therapies, and hospitalization risk among SpA and IBD patients with COVID-19, similar to some studies. 15 - 17 In a study conducted by Bakasis et al 18 , COVID-19 manifestations, outcomes, and antibody responses to SARS-CoV-2 were investigated among patients with autoinflammatory rheumatic diseases.…”
Section: Discussionsupporting
confidence: 86%
“…In most studies, including ours, comorbidities and older age have been found to be independent risk factors for COVID-19-related poor outcomes in patients with IMIDs. 13 , 14 Moreover, we identified no association between baseline treatment, including immunosuppressive therapies, and hospitalization risk among SpA and IBD patients with COVID-19, similar to some studies. 15 - 17 In a study conducted by Bakasis et al 18 , COVID-19 manifestations, outcomes, and antibody responses to SARS-CoV-2 were investigated among patients with autoinflammatory rheumatic diseases.…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown that higher age [ 17 ], cardiovascular, pulmonary and chronic kidney disease were independent risk factors for hospital admission [ 13 , 18 ], while coexisting immune pathologies and increased disease activity raised the odds of severe COVID-19 [ 19 ] and death [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while other cohorts generally reported patients with clinically inactive disease, in our study, 8.4% of patients were undergoing induction therapy and approximately 37% had signs of clinical activity, suggesting that this cohort is characterized by more activity and, therefore, might be at higher risk for SARS-CoV-2-infection. Additionally, the majority of studies undertook a surveillance in patients with autoimmune disorders (including SLE) for SARS-CoV-2 infection that occurred during a short period of observation (ranging 1–9 months) [ 5 , 7 , 8 , 9 , 10 , 18 , 19 , 20 ]. To our knowledge, this is the cohort of patients with SLE and LN with the longest follow-up period spanning the first three waves of the COVID-19 pandemic (mean follow-up 13.5 ± 2 months).…”
Section: Discussionmentioning
confidence: 99%